Towards The Revolutionary Rule Of Law In Nicaragua - Morales Márquez, Odair Marcelo (Scientific journal of social studies, 2025)
This article, using a historical-dogmatic method, aims to present the evolution of the rule of law in Nicaragua. From its inception in the Federal Republic of Central America, the 1824 Constitution already incorporated fundamental principles such as the recognition of basic rights, the rule of law, the separation of powers, and the accountability of officials. These principles were also addressed in the 1826 Constitution, and beginning with the 1838 Constitution, the conception of the State as a political body organized into three branches of government and governed by the principle of administrative legality was consolidated. This evolution intensified with the 1893 Constitution, which introduced secularism and constitutional oversight mechanisms. The Sandinista Popular Revolution promoted the transformation toward a Social State of Law, integrating individual, civil, political, economic, social and cultural rights and, above all, introducing participatory democracy. This process is reflected in the 1987 Constitution, with its respective reforms, which help shape the Revolutionary State of Law, characterized by the predominance of direct democracy, coordination between state bodies and the transformation of social rights to guarantee equality and combat poverty.
Keywords: Revolutionary State of Law; Constitution; Democracy; Social Rights; Sandinista Revolution; Direct participation